2020
DOI: 10.1089/whr.2020.0086
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Fluid in Lipedema and Control Skin

Abstract: Background: Fluid in lymphedema tissue appears histologically as spaces around vessels and between dermal skin fibers. Lipedema is a painful disease of excess loose connective tissue (fat) in limbs, almost exclusively of women, that worsens by stage, increasing lymphedema risk. Many women with lipedema have hypermobile joints suggesting a connective tissue disorder that may affect vessel structure and compliance of tissue resulting in excess fluid entering the interstitial space. It is unclear if excess fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
0
24
0
2
Order By: Relevance
“…As researchers study this phenomenon, I would encourage consideration of the additional possibility that the leaking fluid causes independent damage. Lipedema researchers have found that leakages from microangiopathic blood vessels cause an excess of interstitial fluid that stimulates the formation of subcutaneous adipose tissue [ 3 ], which generates hypoxic conditions and becomes fibrotic, contributing to pain and inflammation [ 4 ].…”
Section: Widespread Pain and Inflammationmentioning
confidence: 99%
“…As researchers study this phenomenon, I would encourage consideration of the additional possibility that the leaking fluid causes independent damage. Lipedema researchers have found that leakages from microangiopathic blood vessels cause an excess of interstitial fluid that stimulates the formation of subcutaneous adipose tissue [ 3 ], which generates hypoxic conditions and becomes fibrotic, contributing to pain and inflammation [ 4 ].…”
Section: Widespread Pain and Inflammationmentioning
confidence: 99%
“…Specifically, elevated macrophages surround adipocytes in lipedema SAT forming adipose crown-like structures were noted [ 87 ]. CD45+ lymphocytes and CD68+ macrophages were also observed in lipedema adipose tissue [ 88 , 89 ] and skin [ 91 ]. However, this infiltrate does not appear to contain the same T cell involvement identified as a key feature seen in lymphedema [ 88 , 89 , 91 ].…”
Section: Molecular Regulators and Pathophysiologymentioning
confidence: 99%
“…CD45+ lymphocytes and CD68+ macrophages were also observed in lipedema adipose tissue [ 88 , 89 ] and skin [ 91 ]. However, this infiltrate does not appear to contain the same T cell involvement identified as a key feature seen in lymphedema [ 88 , 89 , 91 ].…”
Section: Molecular Regulators and Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Microangiopathy associated with the fat growth very early in the disease might lead to a disruption of the endothelial barrier function and to an increase in the permeability of the capillaries [14, 20]. As a result, protein-rich fluid from the vascular system could enter the tissue [21]. In addition, also macroangiopathy develops, which mainly affects the venous vasculature.…”
Section: Introductionmentioning
confidence: 99%